2017
DOI: 10.1021/acs.chemmater.7b02031
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Hexagonal Sheet of TiO2

Abstract: We report on the ab initio discovery of a novel putative ground state for quasi two-dimensional TiO2 through a structural search using the minima hopping method with an artificial neural network potential. The structure is based on a honeycomb lattice and is energetically lower than the experimentally reported lepidocrocite sheet by 7 meV/atom, and merely 13 meV/atom higher in energy than the ground state rutile bulk structure. According to our calculations, the hexagonal sheet is stable against mechanical str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 114 publications
(195 reference statements)
4
57
0
Order By: Relevance
“…They can solve challenging structural problems, as has been demonstrated for the atomic-scale deposition and growth of amorphous carbon films 13 , for proton-transfer mechanisms 14 or dislocations in materials 15,16 , involving thousands of atoms in the simulation. More recently, it was shown that ML potentials can be suitable tools for global structure searches targeting crystalline phases [17][18][19][20] , clusters [21][22][23][24] , and nanostructures 25 .…”
Section: Introductionmentioning
confidence: 99%
“…They can solve challenging structural problems, as has been demonstrated for the atomic-scale deposition and growth of amorphous carbon films 13 , for proton-transfer mechanisms 14 or dislocations in materials 15,16 , involving thousands of atoms in the simulation. More recently, it was shown that ML potentials can be suitable tools for global structure searches targeting crystalline phases [17][18][19][20] , clusters [21][22][23][24] , and nanostructures 25 .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Goedecker and co-workers proposed an environment-dependent charge equilibration scheme for ionic systems, initially introduced for NaCl clusters in the gas phase, [170] constructing a simple force field just from electrostatic terms. [172] The latter structure appears to be interesting due to its electronic band gap, which is much larger than that of known (3D) TiO 2 polymorphs-which might make the material a candidate for photocatalytic hydrogen production, given that a way can be found to synthesize it (e.g., through epitaxial growth on a suitable substrate). [172] The latter structure appears to be interesting due to its electronic band gap, which is much larger than that of known (3D) TiO 2 polymorphs-which might make the material a candidate for photocatalytic hydrogen production, given that a way can be found to synthesize it (e.g., through epitaxial growth on a suitable substrate).…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…Emerging applications of this method deal with surface reconstructions of fluorite-structured materials [173] and the structural prediction of a stable TiO 2 nanosheet (Figure 6c), found in global exploration as accelerated by the ML potential. [172] However, a framework that would "learn" all long-range terms and hierarchically combine this with a short-range fit, thereby making it generally applicable to all kinds of solids (in particular weakly ionic ones), is lacking so far. [172] However, a framework that would "learn" all long-range terms and hierarchically combine this with a short-range fit, thereby making it generally applicable to all kinds of solids (in particular weakly ionic ones), is lacking so far.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations